Can we predict toxicity and efficacy in older patients with cancer? Older patients with colorectal cancer as an example - Winther, Stine Braendegaard (ESMO Open, 2016)
Colorectal cancer is a disease of the elderly. As older and frail patients are under-represented in clinical trials, most of the evidence available on treatment of older metastatic colorectal patients with cancer originates from pooled analyses of the older patients included in large prospective clinical trials and from community-based studies. The aging process is highly individual and cannot be based on the chronological age alone. It is characterised by a decline in organ function with an increased risk of comorbidity and polypharmacy. These issues can result in an increased susceptibility to the complications of both the disease and treatment. Therefore, evaluation of performance status and the chronological age alone is not sufficient, and additionally assessment must be included in the treatment decision process. In the present review, we will focus on clinical aspects of treating older and frail metastatic colorectal patients with cancer, but also on the present knowledge on how to select and tailor therapy for this particular group of patients. TRIAL REGISTRATION NUMBER: EudraCT 2014-000394-39, pre-results.